Yield line analysis of rectangular slabs using contour maps - Pathak, K.K.; Agrawal, Chandresh; Dubey, S.K. (Journal of Structural Engineering, 2024)
In this study contour maps have been developed for fast and reliable yield line analysis of rectangular slabs. Developed based on the data generated using analytical and computational tools, contour maps have been developed using Surfer software. It has been observed that proposed maps offer a powerful tool for the yield line analysis of slabs.